Local practices and production confer resilience to rural Pacific food systems during the COVID-19 pandemic. (March 2022) - Ferguson, Caroline E.; Tuxson, Teri; Mangubhai, Sangeeta; Jupiter, Stacy; Govan, Hugh; Bonito, Victor; Alefaio, Semese; Anjiga, Maxine; Booth, Jonathan; Boslogo, Tracey; Boso, Delvene; Brenier, Ambroise; et al.
Abstract: Resilience of food systems is key to ensuring food security through crisis. The COVID-19 pandemic presents an unprecedented shock that reveals varying levels of resilience of increasingly interconnected food systems across the globe. We contribute to the ongoing debate about whether increased connectivity reduces or enhances resilience in the context of rural Pacific food systems, while examining how communities have adapted to the global shocks associated with the pandemic to ensure food security. We conducted 609 interviews across 199 coastal villages from May to October 2020 in Federated States of Micronesia, Fiji, Palau, Papua New Guinea, Solomon Islands, Tonga, and Tuvalu to understand community-level impacts and adaptations during the first 5–10 months of the COVID-19 crisis. We found that local food production practices and food sharing conferred resilience, and that imported foods could aid or inhibit resilience. Communities in countries more reliant on imports were almost twice as likely to report food insecurity compared to those least reliant. However, in places dealing with a concurrent cyclone, local food systems were impaired, and imported foods proved critical. Our findings suggest that policy in the Pacific should bolster sustainable local food production and practices. Pacific states should avoid becoming overly reliant on food imports, while having measures in place to support food security after disasters, supplementing locally produced and preserved foods with imported foods when necessary. Developing policies that promote resilient food systems can help prepare communities for future shocks, including those anticipated with climate change. Highlights: Most rural Pacific communities were food secure in the early months of the pandemic. Traditional practices of local food production and food sharing conferred resilience. Increasing food production, in particular agriculture, was the main way people adapted. Natural disasters reduced the capacity to increase local food production in affected villages. Bolstering local food practices is key for supporting food security in rural Pacific communities.